2020
DOI: 10.1155/2020/6697577
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from Human Urine-Derived Stem Cells Inhibit Intervertebral Disc Degeneration by Ameliorating Endoplasmic Reticulum Stress

Abstract: Objective. This study is aimed at determining the effects of human urine-derived stem cell-derived exosomes (USCs-exos) on pressure-induced nucleus pulposus cell (NPC) apoptosis and intervertebral disc degeneration (IDD) and on the ERK and AKT signaling pathways. Methods. The NPCs were obtained from patients with herniated lumbar discs. Western blot analysis (WB) and quantitative real-time polymerase chain reaction (qRT-PCR) were used to determine endoplasmic reticulum (ER) stress levels of NPCs under stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 88 publications
0
28
0
Order By: Relevance
“…In the previous study [ 20 ], the team studied the effect of USC-exos on intervertebral disc degeneration by inhibiting the apoptosis of NPCs. We now further explored the promotion of cell proliferation and ECM modulatory effects of human urine-derived stem cell (USC) exosomes (USC-exos) on degenerated intervertebral discs in cell and rat models and explored the underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study [ 20 ], the team studied the effect of USC-exos on intervertebral disc degeneration by inhibiting the apoptosis of NPCs. We now further explored the promotion of cell proliferation and ECM modulatory effects of human urine-derived stem cell (USC) exosomes (USC-exos) on degenerated intervertebral discs in cell and rat models and explored the underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The International Society for Cellular Therapy (ISCT) proposed that MSCs be identified by the following markers: 1) the cells can adhere to plastic culture bottles; 2) at least 95% of the cell population expresses specific surface antigens, including CD105, CD73 and CD90, and do not express CD45, CD34, CD14, CD11b, CD79α, CD19 or HLA-II antigens; and 3) the cells can be differentiated into OBs, chondroblasts and adipocytes under appropriate conditions ( Dominici et al, 2006 ). Because USCs meet the criteria for MSCs, isolated USCs may express similar typical surface markers, such as CD29, CD44, CD54, CD73, CD90, CD166 and STRO-1 ( Bharadwaj et al, 2013 ; Li et al, 2020 ; Xiang et al, 2020 ). In addition, pericyte (CD146) ( Bharadwaj et al, 2013 ), epithelial (E-cadherin, claudin 1 and occludin), fibroblast (vimentin and fibronectin) and renal epithelial (L1CAM and NR3C2) ( Kim et al, 2020b ) markers are expressed in USCs.…”
Section: Isolation and Culture Of Uscsmentioning
confidence: 99%
“…For example, Cheng et al [ 109 ] reported that BMSC-derived EVs can inhibit NP cell apoptosis and reduce IVDD through miR-21. Xiang et al [ 110 ] and Liao et al [ 111 ], respectively, demonstrated that MSC-derived EVs can attenuate ER stress-induced NP cell apoptosis and retarded IDD progression in a rat model. Besides, Hingert et al [ 112 ] treated human degenerated disc cells with MSC-derived EVs in vitro and saw more than a 50% increase in cell proliferation and a decrease in apoptosis.…”
Section: Ivd Progenitor Cells In Disc Regenerationmentioning
confidence: 99%